Aging and IGF-I: relationships with vitamin D and body composition. A mediation analysis - Vicinanza, Roberto; Frizza, Alessandro; Pollard, Julie A.; Mazza, Valentina; De Martino, Massimo Ulderico; Imbimbo, Giovanni; Pignatelli, Pasquale; Ettorre, Evaristo; Del Ben, Maria; Molfino, Alessio (Frontiers in Nutrition, 2025)
BackgroundInsulin-like Growth Factor I (IGF-I) and Vitamin D are crucial for growth and metabolism, with their levels declining with age. However, their mutual interactions and contributions to body composition remain unclear.ObjectivesTo examine the relationships between IGF-I, Vitamin D, and body composition in geriatric outpatients, and to test the mediational role of IGF-I in the association between Vitamin D and Fat-Free Mass (FFM).MethodsOne hundred thirty patients were eligible at the Geriatric Outpatient Clinic at the Policlinico Umberto I, Sapienza University of Rome, Italy. Multimorbidity was evaluated with the Cumulative Illness Rating scale for Geriatrics (CIRS-G). Body composition was measured using bioelectrical impedance analysis. Complete blood count, metabolic panel, IGF-I, and 25(OH) Vitamin D were assessed.ResultsNinety-one patients were included in the analysis. Mean age was 74.4 ± 7.2 years; 50.5% female. Mean BMI was 28 kg/m2 ± 3.9. Mean CIRS-G total score was 14.14 ± 4.1, and Severity Index (SI) was 1.16 ± 0.32. Median IGF-I was 122.0 ng/mL (IQR, 69.8) with higher levels in males compared to females (p = 0.0096). Mean 25(OH) Vitamin D was 27.04 ng/mL ± 14.69 with no significant sex difference. Level of 25(OH) Vitamin D positively correlated with IGF-I (ρ = 0.317, p = 0.003), while no correlation was found between Vitamin D and body composition parameters. Patients with higher IGF-I exhibited higher Total Body Water (TBW) (p = 0.024), Intracellular Water (ICW) (p = 0.018), FFM (p = 0.022), and Muscle Mass (MM) (p = 0.017), Body Cell Mass (BCM) (p = 0.046). Linear regression analysis showed that IGF-I and male sex predicted FFM (B = 13.933, p < 0.001; B = 0.040; p = 0.034; respectively). The mediation analysis confirmed no significant direct effect of Vitamin D on FFM (direct effect, B = −0.058, p = 0.319, 95% CI: −0.175, 0.058); however, the effect was significant when mediated by IGF-I (indirect effect, B = 0.039, SE = 0.022, 95% CI: 0.005, 0.091).ConclusionThese findings provide further evidence of a positive correlation between IGF-I and lean body mass and suggest that IGF-I may mediate the physiological effect of Vitamin D on FFM, highlighting their potential roles in assessing pre-frailty and personalizing nutrition interventions.